LEXICAL AND GRAMMATICAL CATEGORIES OF NOUNS - Nurmukhamedova Mokhera Uralovna (Academia Science Repository, 2023)
This article is devoted to lexical and grammatical categories of nouns. Lexico-grammatical classes are analyzed based on the prototypical properties of certain names. It is also established that concrete nouns are opposed to abstract ones through collective nouns that have the characteristics of both concrete and abstract nouns.